Fan Resistance Towards a Change in Club Identity - Pauwels Delassus, Véronique; Mogos Descotes, Raluca (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2018)
The objective of the research is to identify key factors that can reduce resistance towards a change in club identity. The results of our quantitative approach conducted with 229 fans of football clubs show that it is extremely important to inform supporters about the reasons and the benefits of the brand identity change, for the club and for themselves. Furthermore, the fans’ tradition consciousness amplifies their resistance to brand identity change. Our results also indicate that after the brand identity change, fans limit the positive word of mouth towards the club (a form of passive resistance) and then exit (a form of active resistance).